2012
DOI: 10.5194/tc-6-353-2012
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface climate and surface energy budget of Larsen C ice shelf, Antarctic Peninsula

Abstract: Abstract. Data collected by two automatic weather stations (AWS) on the Larsen C ice shelf, Antarctica, between 22 January 2009 and 1 February 2011 are analyzed and used as input for a model that computes the surface energy budget (SEB), which includes melt energy. The two AWSs are separated by about 70 km in the north-south direction, and both the near-surface meteorology and the SEB show similarities, although small differences in all components (most notably the melt flux) can be seen. The impact of subsurf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 26 publications
7
121
1
Order By: Relevance
“…2). The value on LCIS compares well with that of about 20 cm (8.7 Wm −2 ) measured by Kuipers Munneke et al (2012Munneke et al ( ) in 2009Munneke et al ( -2011. For WIS we obtained 36-73 melt days per summer and the melt varied from 10 to 23 cm w.e.…”
Section: Summertime Surface Meltingsupporting
confidence: 76%
See 4 more Smart Citations
“…2). The value on LCIS compares well with that of about 20 cm (8.7 Wm −2 ) measured by Kuipers Munneke et al (2012Munneke et al ( ) in 2009Munneke et al ( -2011. For WIS we obtained 36-73 melt days per summer and the melt varied from 10 to 23 cm w.e.…”
Section: Summertime Surface Meltingsupporting
confidence: 76%
“…The warm-air advection together with large downward longwave radiation under extensive cloud cover contributed to the high air and snow surface temperatures on LCIS. Also, previous studies have indicated that high temperatures on Larsen Ice Shelf were found together with north-westerly winds (Kuipers Munneke et al, 2012) and the breakup of Larsen B Ice Shelf in 2002 was preceded by northwesterly winds (van den Broeke, 2005). During the winter with anomalously small surface net energy flux, the mean sea level pressure was higher than during the winters when the surface net flux was close to the long term average.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations